34.7k views
4 votes
The temperature dropped -4° F on Monday, -5° F on Tuesday, and -3° F on Wednesday. Which equation correctly shows how to find the average drop in temperature for all three days? (-4) + (-5) + (-3) = 12 12 ÷ 3 = 4 (-4) + (-5) + (-3) = -12 -12 ÷ 3 = -4 (-4) + (-5) + (-3) = 12 12 ÷ -3 = -4 (-4) + (-5) + (-3) = -12 -12 ÷ -3 = 4

User Iesus
by
5.6k points

2 Answers

1 vote

Answer:

(-4) + (-5) + (-3) = -12

-12 ÷ 3 = -4

Explanation:

First find the total number of degrees the temperature dropped. The signs are all the same, so add and keep the sign. Divide the total number of degrees the temperature dropped by 3 to find the average number of degrees dropped for all three days.

User Sayed
by
5.5k points
2 votes
There are actually two equations involved. One to find the sum of the temperature changes; the other to compute the average from that sum. The average is computed by dividing the sum by the number of terms (3). The number of terms is a count of obects, so will not be negative.

The appropriate choice is ...
(-4) + (-5) + (-3) = -12 -12 ÷ 3 = -4
User Habax
by
6.2k points